2021
DOI: 10.3892/mmr.2021.11940
|View full text |Cite
|
Sign up to set email alerts
|

Dual PI3K/mTOR inhibitor NVP‑BEZ235 decreases the proliferation of doxorubicin‑resistant K562 cells

Abstract: Acute myelogenous leukemia (AML) is frequently accompanied by a poor prognosis. The majority of patients with AML will experience recurrence due to multiple drug resistance. Our previous study reported that targeting the mTOR pathway may increase cell sensitivity to doxorubicin (Doxo) and provide an improved therapeutic approach to leukemia. However, the effect and mechanism of action of NVP-BEZ235 (BEZ235), a dual inhibitor of PI3K/mTOR, on Doxo-resistant K562 cells (K562/A) is yet to be elucidated. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…Its activation promotes cell cycle progression by downregulation of cyclin D1, maintains cell survival through inactivation of Bad meanwhile increase of the expression of Bcl-2 protein, and promotes cell growth by phosphorylation of the downstream mTOR. Treated with FD268, our studies documented the reduction of PI3K/Akt process and downregulation in the level of phosphorylated mTOR as well as its downstream targets p70S6K at Thr389 and 4EBP1 in both HL-60 and MOLM-16 cells, which is in agreement with those well-known PI3K inhibitors in treatment of AML [ 26 , 46 , 47 ]. Although it is hard to reveal the cell-line-dependent regulation of cell cycle arrest and completely map the mechanisms of actions in AML, our studies, together with KEGG pathway analysis, demonstrated the capacity of FD268 in suppressing cell proliferation and inducing apoptosis on AML through inhibition of PI3K/Akt/mTOR signaling pathway ( Fig 9 ).…”
Section: Discussionsupporting
confidence: 88%
“…Its activation promotes cell cycle progression by downregulation of cyclin D1, maintains cell survival through inactivation of Bad meanwhile increase of the expression of Bcl-2 protein, and promotes cell growth by phosphorylation of the downstream mTOR. Treated with FD268, our studies documented the reduction of PI3K/Akt process and downregulation in the level of phosphorylated mTOR as well as its downstream targets p70S6K at Thr389 and 4EBP1 in both HL-60 and MOLM-16 cells, which is in agreement with those well-known PI3K inhibitors in treatment of AML [ 26 , 46 , 47 ]. Although it is hard to reveal the cell-line-dependent regulation of cell cycle arrest and completely map the mechanisms of actions in AML, our studies, together with KEGG pathway analysis, demonstrated the capacity of FD268 in suppressing cell proliferation and inducing apoptosis on AML through inhibition of PI3K/Akt/mTOR signaling pathway ( Fig 9 ).…”
Section: Discussionsupporting
confidence: 88%
“…BEZ235 treatment decreased proliferation and confluency in TdTomato-4T1 cells, with treated cells showing reduced rates of proliferation over 5 days compared to untreated cells (Fig 3 .6A, B). BEZ235 therefore had an effect on TdTomato-4T1 proliferation, consistent with literature and the cytostatic mechanism of action of BEZ235 214,215 . Fluctuations in confluency measurements were seen in the 1.2µM treated conditions.…”
Section: Discussionsupporting
confidence: 88%
“…The mTOR kinase is responsible for phosphorylating downstream proteins, such as AKT, which are recognized as significant in promoting cancer growth 29,30 . Small‐molecule inhibitors that have been developed and extensively validated for their tumor‐suppressing effects target the PI3K/mTOR pathway 13,31,32 . The activation of the PI3K/AKT/mTOR pathway has been reported in AML cells, 13,33 and targeting this signaling pathway has demonstrated beneficial therapeutic effects on AML both in vitro and in vivo 13,34 .…”
Section: Discussionmentioning
confidence: 99%